Fenomena Prostitusi Dengan Menggunakan Aplikasi MiChat Di Kota Sorong - Hamid, Farhan; Djamali , Dayan; Ahriani , Andi (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2024)
Online prostitution via the MiChat application has become a widespread problem in Sorong City, West Papua, Indonesia. This phenomenon involves individuals offering sexual services in exchange for money, using the MiChat app to connect with potential clients. This practice has raised concerns among local authorities and community members due to its negative impact on society, including exploitation of vulnerable individuals, spread of sexually transmitted infections, and disruption of social norms. To address this problem effectively, a comprehensive approach is needed. Law enforcement agencies must continue to crack down on online prostitution rings and arrest those involved. Additionally, educational programs and awareness campaigns should be implemented to inform the public about the dangers of online prostitution and promote positive alternatives. Furthermore, support services should be provided to assist victims of exploitation and assist them in returning to society. By tackling online prostitution through a multidimensional approach, the City of Sorong can work to create a safer and fairer environment for all.